Upaya Pencegahan dan Penanganan Masalah Tindak Pidana Perdagangan Orang Ditinjau dari Perda Kota Kupang Nomor 3 Tahun 2019 tentang Pencegahan dan Penanganan Masalah Tindak Pidana Perdagangan Orang - Adrya Gusmar Kapitan; Aksi Sinurat; Adrianus Djara Dima (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The purpose of this research is to analyze the efforts to prevent and handle the problem of human trafficking in review of kupang city regional regulation number 3 of 2019 concerning the prevention and handling of the problem of human trafficking. This research is an empirical juridical research method. The result of this research is that the Government and the Task Force on Human Trafficking have made various efforts in preventing and handling the problem of Human Trafficking in Kupang City by referring to Kupang City Regional Regulation Number 3 of 2019 and in the process of preventing and handling the problem of Human Trafficking in Kupang City there are several obstacles. The conclusion of this research is that the efforts to prevent and handle the problem of trafficking in persons carried out by the Kupang City Government and the Task Force for Trafficking in Persons have not been fully implemented in accordance with Kupang City Regional Regulation Number 3 of 2019, namely not implementing Administrative Control of Population Mutation and Migration, Control of Labor Placement, and Early Detection. Constraints experienced: a. Suboptimal Inter-Agency Coordination; b. Allocation of Meeting Time between Task Force Members is not optimal; c. Lack of Socialization at the Central and Regional Stakeholder Levels; d. Human Resources (HR) are Still Low. Inadequate Human Resources (HR); and e. Misuse of Technology and Information. The first suggestion is that the Kupang City Government and the Trafficking in Persons Task Force should implement activities to prevent and handle the problem of trafficking in persons in accordance with Kupang City Regional Regulation No. 3/2019 in full, namely by implementing activities to control the administration of population mutation and migration, control labor placement, and early detection. The second suggestion is that the Kupang City Government and the Human Trafficking Task Force should increase the number of inter-agency coordination meetings to unify the vision and mission of the Task Force in combating human trafficking.